Exposure to ambient air pollution and indicators of maternal liver function during pregnancy: Findings from a birth cohort study in Foshan City, Southern China. (15th December 2022) - Yang, Yin; Lin, Qingmei; Liang, Ying; Ma, Liming; Zhang, Shiyu; Lai, Zhihan; Qian, Zhengmin (Min); McMillin, Stephen Edward; Howard, Steven W.; Wu, Xueli; Luo, Weidong; Zhang, Zilong; et al.
Abstract: Evidence concerning the associations between gestational air pollution exposure and maternal liver function is scarce. We explored this topic by analyzing data from a birth cohort study conducted in Foshan city, Southern China. Between 2015 and 2019, we recruited a total of 49, 568 pregnant women from 16 hospitals in Foshan city. Basic socio-demographical information and lifestyle factors was collected from the hospital medical records. Daily PM2.5, PM10, SO2, NO2, and O3 exposure of each participant during study period was assessed by inverse-distance weighted method. Then, we assigned the average air pollutant levels during trimester 1, trimester 2, and the first two trimesters to each participant. Liver function indicators (liver enzymes, serum protein, and serum bilirubin) of each participant were measured during their third trimester prenatal visit. Mixed-effects linear and logistic regression models were used to evaluate the associations of gestational air pollution exposure and maternal liver function indicators. Our findings suggested that maternal exposure to air pollution during pregnancy, especially trimester 2, was associated with increased liver enzyme levels and decreased serum protein levels. Graphical abstract: Image 1 Highlights: A total of 49, 568 pregnant women from Foshan City, Southern China were recruited. Liver enzyme, serum protein and bilirubin were measured to indicate liver function. Gestational air pollution exposure was associated with increased liver enzymes. Gestational air pollution exposure was associated with decreased serum protein levels. Trimester 2 might be the critical exposure window.